2014 — The Year of Significant Dates in the History of Anatomy in Russia - A. I. Shvedavchenko; V. A. Kudryashova; M. V. Oganesyan; N. A. Rizaeva (Сеченовский вестник)
2014 was remembered in the history of anatomy by the following important dates: the world community celebrated 500 years since the birth of A. Vesalius, the great anatomist of the Renaissance, the 250-th anniversary of the founding of the Department of human anatomy of the I.M. Sechenov First Moscow State Medical University and 150 years since the birth of professor P.I. Karuzin. 2014 was a signifi cant year for the St. Petersburg school of anatomy: marked the 250-th anniversary of P.A. Zagorsky’s birth and 200 years since the birth of the famous anatomist of the XIX-th century V.L. Gruber.